PENGARUH KERJA SHIFT DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS MAHASISWA STEIN YANG BEKERJA DI HOTEL - Verry Cyasmoro (LPPM Universitas Asa Indonesia, 2015)
This study aims to determine the relationship between shift work and working environment on the productivity of the employees of the Hotel Jakarta. The type of research is explanatory, with data collection through a questionnaire. The total sample of 90 respondents drawn by random sampling technique. While analysis of the data using qualitative and quantitative way by hypothesis testing with statistical tests, among others, product moment correlation test, T-test and the coefficient of determination. The conclusions drawn that the policy shift work system and work environment positive impact on the productivity of employees working at the hotel in Jakarta. It is therefore suggested that the policy shift working system and the work environment can be improved so that the hotel employee productivity continues to increase.